How Can Bulgaria Improve Its Education System? An Analysis of PISA 2012 and Past Results - World Bank (Washington, DC, 2014)
Bulgaria's performance on all three disciplines of the program for international student assessment (PISA) 2012 was slightly better than its PISA 2000 performance, after having dropped between 2000 and 2006. The improvements in performance between 2006 and 2012 promoted shared prosperity, but equality of opportunities is still a major challenge. In fact, disaggregating students' PISA scores across a number of variables for example, location and ethnicity - shows that large inequalities exist in Bulgaria's education system. Peer characteristics and school segregation are the key drivers of the Bulgarian education system's performance. An in-depth analysis into math and reading skills shows imbalances in performance in Bulgaria. The main areas in which Bulgaria can further improve its educational system involve: delaying the tracking of students to reduce segregation in schools; continue improving the quality of educational resources to ensure that all students learn in an environment with books, lab equipment, and technological hardware and software; encouraging longer pre-primary education for all children; learning from successful schools to improve accountability mechanisms for schools countrywide, particularly in rural areas; reevaluating the curriculum and assessment framework to better align student learning to the envisaged country goals; and promoting effective classroom management and strengthening teaching practices.